E-Ticketing System and Integration with Third Parties Scrum-Based - Jimmy Sentosa; Maharina Maharina; Chandra Zonyfar (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
SCRUM is a software development life cycle that will work with collaboration to produce products quickly but still provide quality. By using SCRUM, it will increase productivity and increase mutual trust, togetherness, responsibility, ideas communication and creativity of team members. The stakeholder's expectation to build an e-ticketing system fits with the agile nature of SCRUM. Every process in SCRUM must run well starting from data collection, needs analysis, making product backlog, making sprint backlog, daily scrum meeting, sprint review until sprint retrospective must be carried out to achieve success. The applications built in this research will run on web browsers, android and API designs to be integrated with other applications. The research was conducted for two months by working on three product backlogs, then each product backlog would be broken down into three sprints. The results obtained in the study were able to answer the question of the problem that was built with the conclusion that the product owner's ability to communicate with stakeholders and daily scrum meetings was necessary indetermining success in SCRUM